2xÂ² + x - 3 = 0

Step-by-step explanation:

Basta. Katamad magtype dito sa papel ko sinolve

I know only the answer in 1 to 3. In 4 and 5, I'm still confuse.

1. B

2. C

3. C

I think, to transform it into a quadratic equation, it should be

x(x-6)=16 not x(a-6)=16

if we transform x(x-6)=16, it will be xÂ²-6x=16 or xÂ²-6x-16=0 when written in standard form..

to transform, use distributive property

hope it will help

Transform the equation in standard form ax^2 + bx + c = 0 (1) into a new equation, with a = 1, and the constant C = a*c. The new equation has the form: x^2 + bx + a*c = 0, (2).

Transform the equation in standard form ax^2 + bx + c = 0 (1) into a new equation, with a = 1, and the constant C = a*c. The new equation has the form: x^2 + bx + a*c = 0, (2). Solve the transformed equation (2) by the Diagonal Sum Method that can immediately obtain the 2 real roots

Step-by-step explanation:

sana po makatulong